Frequency and Severity of Facial Injuries in Cyclists A Comparative Study from the Years 1980-1982 and 2000-2002 - J. Šimek; J. Pazdera; P. Tvrdý (Czech Dental Chamber, 2005)
The authors analyze medical documentation of patients, hospitalized and treated at the Clinical of Oral, Jaw and Facial Surgery, Faculty Hospital and Medical Faculty of Palacky University in Olomouc in the years 1980-1982 and 2000-2002. In the three-year period at the beginning of 80ties, 32 injured cyclists were treated at the clinic and twenty years later there were 112 patients, i.e. 3.5-fold more. Most injuries occurred during summer months, on weekends and in the evenings. The mean age of the injured persons increased over the twenty years from 33.3 years to 37.3 years. The severity of the facial injuries increased as well. In addition to injuries of soft tissues, fractures of mandible condylar processes were the most frequent traumas.The main causes of the increasing trends in facial injuries of cyclists are apparently the imperfect technique of riding, absent protective remedies for passive safety, increased traffic on the roads, carelessness and frequently also ruthlessness of the participants.